Study about the focus of attention in junior athletes of rhythmic gymnastics - Mercedes Lourdes Pérez Iznaga; Marta Cañizares Hernández; Isabel Fleitas Díaz; Alessandro D`Amico López (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2018)
Psychological preparation is one of the pillars on which the overall preparation of the athlete is based; This must start from the individual or group psychological diagnosis and incorporate the work of the trainer. The attention, in the case of the Rhythmic Gymnastics, demands a high concentration, being one of the essential aspects to reach the maximum level in the different dimensions that constitute the performance (quality of execution, technical level and artistic level).The present investigation has as precedent studies of this author on psychological analysis in the gymnasts, supported by the scientific project "Psychological Attention to the School Sportsman" of the Center of Psychology Studies of the Physical Activity and Sports and has as objective to make a diagnosis on the concentration of attention in the Havana gymnasts and the treatment received by the coaches. To this end, research methods such as document analysis, surveys, interviews and observations were used to obtain information from different sources. The main results of the study revealed insufficiencies that in this sense appear in the gymnasts, caused by different internal and external distracters, and the need for training and overcoming of the trainers to contribute to the improvement of this psychological process.